Shock propagation through a bubbly liquid in a deformable tube - ANDO, KEITA; SANADA, T.; INABA, K.; DAMAZO, J. S.; SHEPHERD, J. E.; COLONIUS, T.; BRENNEN, C. E. (Journal of fluid mechanics, 2011)
Shock propagation through a bubbly liquid contained in a deformable tube is considered. Quasi-one-dimensional mixture-averaged flow equations that include fluid–structure interaction are formulated. The steady shock relations are derived and the nonlinear effect due to the gas-phase compressibility is examined. Experiments are conducted in which a free-falling steel projectile impacts the top of an air/water mixture in a polycarbonate tube, and stress waves in the tube material and pressure on the tube wall are measured. The experimental data indicate that the linear theory is incapable of properly predicting the propagation speeds of finite-amplitude waves in a mixture-filled tube; the shock theory is found to more accurately estimate the measured wave speeds.